Informasi Lowongan Kerja Wilayah Kabupaten Sumbawa Berbasis Android - Indah Putrianti; Shinta Esabella; Rizka Irjiba (Bulletin of Information Technology (BIT), 2022)
Searching for job vacancies in the Sumbawa Regency area is currently obtained through social media such as Facebook, Instagram, and special applications for job vacancies that can be downloaded via the play store. However, this method is less effective because it takes time to gather information on job vacancies that match the criteria that everyone has. For this reason, it is necessary to build an Android-based Job Vacancies Information Application for Sumbawa Regency. With the aim of producing an android-based application for job vacancies in the Sumbawa Regency area that makes it easier for job seekers and job vacancies providers in the Sumbawa Regency area. This research uses qualitative research methods and SDLC (System Development Life Circle) development methods with the Spiral model. The application is built using the dart programming language, uses the flutter framework, and uses the visual studio code editor, and uses the MariaDB database with the help of a local Xampp server. The application has also been tested using Black-box testing